Наукові та практичні аспекти застосування інформаційної системи оцінки виробничого ризику - Кружилко, О. Є.; Богданова, О. В. (Техніка будівництва, 2020)
The article describes the main scientific principles to the estimation of production risk. For automated calculation of the production risk level developed by the appropriate information system. Describes the recommendations on practical use of tools for assessment of industrial risks. It was found that the implementation of a risk-oriented approach implies the existence of appropriate information systems that will automate the process of settlement in all stages of planning to reduce production risk.